DETERMINING THE STAGES AND FACTORS IN RELATION TO THE SECOND LANGUAGE ACQUISITION OF KINDERGARTEN STUDENTS - Halili, Ynna (PEOPLE: International Journal of Social Sciences, 2017)
The research was conducted to determine the stages of second language development that correlates on the age of the subjects. Also, to identify other internal and external factors that affects the second language acquisition in Kindergarten. The Descriptive-Qualitative Method was used in this study. Gathering of data are done through execution of researcher-made tasks, observations, interviews, and document reviews. The subjects are asked to complete the researcher-made tasks and interview individually. The outcome of this study is that the acquisition of the second language may progress at faster or slower rates depending on the presence of internal and external factors and students who were provided with enough exposure can beat those who don’t have the opportunity for interaction. For future researches, provide an intervention that is applicable to the current K-12 Curriculum which can offer exposure and access to the second language. Additionally, assessment and evaluation of the researcher-made tasks were recommended for authenticity.